Polymer Conjugate as the New Promising Drug Delivery System for Combination Therapy against Cancer - Hu, Qiang; Zhang, Yuannian; Mukerabigwi, Jean Felix; Wang, Haili; Cao, Yu (Current Topics in Medicinal Chemistry, 2024)
This review highlights the advantages of combination therapy using polymer conjugates as drug delivery systems for cancer treatment. In this review, the specific structures and materials of polymer conjugates, as well as the different types of combination chemotherapy strategies, are discussed. Specific targeting strategies, such as monoclonal antibody therapy and small molecule ligands, are also explored. Additionally, self-assembled polymer micelles and overcoming multidrug resistance are described as potential strategies for combination therapy. The assessment of combinational therapeutic efficacy and the challenges associated with polymer conjugates are also addressed. The future outlook aims to overcome these challenges and improve the effectiveness of drug delivery systems for combination therapy. The conclusion emphasizes the potential of polymer conjugates in combination therapy while acknowledging the need for further research and development in this field.
Keywords: Polymer conjugate